Using farmer decision”“making profiles and managerial capacity as predictors of farm viability in Argentinean dairy farms (la Pampa). - Perea, José; de Pablos Heredero, Carmen; Angón, Elena; Giorgis, Alberto; Barba, Cecilio; García, Antón (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
The aim of this study was to evaluate the effect of management on the economic viability of the dairy farms in La Pampa (Argentina). Between 2005 and 2007 the owners/managers of 57 dairy farms were interviewed by stratified randomized sampling with proportional assignation. It was analyzed 22 variables related to the decision”“making process, farm features and personal aspects of the farmer/manager were analyzed. The farms were divided into viable or unviable regarding their ability to generate profits. A logistic regression model was used to determine variables related to the viability of the farm and its functioning. Results showed that the farm size (OR=1.006), the compilation of farming records (OR=5.928), the use of external information (OR=5.910) and external advisors (OR=5.738) in the farm decision”“making were significant predictors of the farm”™s viability, being particularly relevant the influence of management on the economic yield of the farm.